Validation of the hospital frailty risk score in a tertiary care hospital in Switzerland: results of a prospective, observational study. Issue 1 (15th January 2019) - Eckart, Andreas; Hauser, Stephanie Isabelle; Haubitz, Sebastian; Struja, Tristan; Kutz, Alexander; Koch, Daniel; Neeser, Olivia; Meier, Marc A; Mueller, Beat; Schuetz, Philipp
Abstract : Objectives: Recently, the Hospital Frailty Risk Score based on a derivation and validation study in the UK has been proposed as a low-cost, systematic screening tool to identify older, frail patients who are at a greater risk of adverse outcomes and for whom a frailty-attuned approach might be useful. We aimed to validate this Score in an independent cohort in Switzerland. Design: Secondary analysis of a prospective, observational study (TRIAGE study). Setting: One 600-bed tertiary care hospital in Aarau, Switzerland. Participants: Consecutive medical inpatients aged ≥75 years that presented to the emergency department or were electively admitted between October 2015 and April 2018. Primary and secondary outcome measures: The primary endpoint was all-cause 30-day mortality. Secondary endpoints were length of hospital stay, hospital readmission, functional impairment and quality of life measures. We used multivariate regression analyses. Results: Of 4957 included patients, 3150 (63.5%) were classified as low risk, 1663 (33.5%) intermediate risk, and 144 (2.9%) high risk for frailty. Compared with the low-risk group, patients in the moderate risk and high-risk groups had increased risk for 30-day mortality (OR (OR) 2.53, 95% CI 2.09 to 3.06, p<0.001 and OR 4.40, 95% CI 2.94 to 6.57, p<0.001) with overall moderate discrimination (area under the ROC curve 0.66). The results remained robust after adjustment for important confounders. Similarly, we found longer length of hospital stay, more severe functional impairment and a lower quality of life in higher risk group patients. Conclusion: Our data confirm the prognostic value of the Hospital Frailty Risk Score to identify older, frail people at risk for mortality and adverse outcomes in an independent patient population. Trial registration number: NCT01768494; Post-results.